Preparation of new Iraqi paving oxidation asphalt using local additives - Jasim Mohammed Salman (Journal of Madenat Alelem University College, 2022)
The asphalt (40-50) produced in the Dora refinery (which does not conform to the specifications of the surface layer according to the Iraqi roads and bridges amended regulations for 2003) was approved as a raw material for the preparation of new oxidized Iraqi asphalt with high mechanical and physical properties by adding some local chemical and polymeric additives to increase the hardness of the asphalt mixture.The study included treating the asphalt received from the Dora refinery by blowing with air for different periods, then mixed with sulfur, rubber, activated carbon and polymeric additives with different weight ratios and different mixing times to prepare oxidized asphalt. The results of the laboratory examination showed a clear development in the homogeneity of the prepared oxidized asphalt, giving it excellent specifications in terms of acceptance.